2015
DOI: 10.1371/journal.pone.0134764
|View full text |Cite
|
Sign up to set email alerts
|

High Sodium-Induced Oxidative Stress and Poor Anticrystallization Defense Aggravate Calcium Oxalate Crystal Formation in Rat Hyperoxaluric Kidneys

Abstract: Enhanced sodium excretion is associated with intrarenal oxidative stress. The present study evaluated whether oxidative stress caused by high sodium (HS) may be involved in calcium oxalate crystal formation. Male rats were fed a sodium-depleted diet. Normal-sodium and HS diets were achieved by providing drinking water containing 0.3% and 3% NaCl, respectively. Rats were fed a sodium-depleted diet with 5% hydroxyl-L-proline (HP) for 7 and 42 days to induce hyperoxaluria and/or calcium oxalate deposition. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…Further, some studies have shown that high sodium intake induces intra-renal oxidative stress via increased NAD(P)H oxidase (NOX) activity and decreased expression of superoxide dismutase (SOD) [62]. And also increases the urinary elimination of calcium in proportion to sodium and water via reduced passive reabsorption of calcium [63]. As calcium transport is closely linked to sodium transport in renal tubules, high dietary sodium tends to decrease calcium reabsorption and increase calcium excretion via urine leading to a temporary decrease in serum calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Further, some studies have shown that high sodium intake induces intra-renal oxidative stress via increased NAD(P)H oxidase (NOX) activity and decreased expression of superoxide dismutase (SOD) [62]. And also increases the urinary elimination of calcium in proportion to sodium and water via reduced passive reabsorption of calcium [63]. As calcium transport is closely linked to sodium transport in renal tubules, high dietary sodium tends to decrease calcium reabsorption and increase calcium excretion via urine leading to a temporary decrease in serum calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, the HS diet induces intrarenal oxidative stress by elevating the NADPH oxidase activity . The HS diet enhances crystal deposition because of the elevation of AP (CaOx) and oxidative stress . In rats, chronic treatment with aldosterone and a HS diet caused severe proteinuria and renal tissue injury characterized by glomerulosclerosis and tubulointerstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both animal [22,23] and clinical studies [3] have demonstrated that increases in oxidative stress in the kidneys of stone-forming patients and animals is indicated by the urinary excretion of ROS, the production of lipid peroxidation, and renal tubular enzymuria. An in vitro cell culture study showed that exposure to crystals, CaOx, and CaP leads to the development of oxidative stress [24].…”
Section: The Link Connecting Atherosclerosis and Kidney Stone Formationmentioning
confidence: 99%